The effectiveness of physical and skill exercises in a hot atmosphere and its effect on the response of some physiological indicators and the level of achievement of the air rifle competition juniors - Abdul Hameed, Ghusoon Natiq (International Journal of Psychosocial Rehabilitation, 2020)
The importance of preparing training programs and medical examinations for the players periodically and this is what makes them at the required level and training the players in different atmospheres on a regular basis in the training units to obtain the important physiological adaptations that contributed to the development and codification of the training loads so that it is appropriate to the ability of the body and benefit from its positive effects and avoid negative effects in The state of health, that the formation of a training load without studying its physiological effects in the body sometimes leads to a lot of burden on the body's organs according to the regulation of training loads, which gives physiological adaptations to the internal load whose results are reflected in the high level of athletic performance, which leads to the efficiency of the functional devices that increase The effectiveness of muscular work, and the goal of the research is to:• Preparing skillful physical exercises in hot climates and their effect on response to some physiological indicators and the level of achievement in the effectiveness of air rifle shooting.• Identify the effectiveness of skillful physical exercises in hot climates and their effect in response to some physiological indicators and the level of achievement in the effectiveness of air rifle shooting between the pre and post tests of the research group.• Identify the differences between the control and experimental groups in the telemetry tests in response to some physiological indicators and the level of achievement of air rifle shooting buddies.As for the research hypotheses: • There are statistically significant significant differences between the pre and post tests in the physiological indicators and the level of achievement in the effectiveness of air rifle shooting and in favor of the post tests for members of the experimental and control groups.• There are statistically significant differences between the experimental and control groups in the dimensional tests in physiological indicators and the level of achievement in the effectiveness of air rifle shooting in favor of the experimental group.The two researchers adopted the experimental approach with equal groups and determined the research community for the Air Rifle Competition for junior girls with (10) players aged 15-16 years. Physical and skill exercises were applied in a hot atmosphere to the experimental group for a period of eight weeks and at three training units per week. The two researchers used the latest version of ( IBM SPSS Statistics Version25) to process data and the two researchers reached the most important conclusions that physical and skill training has positively affected the response to some physiological indicators and the level of achievement of the female air rifle competition juniors. Achievement.